2023
DOI: 10.2147/ccid.s391667
|View full text |Cite
|
Sign up to set email alerts
|

Passive Enhancement of Retinol Skin Penetration by Jojoba Oil Measured Using the Skin Parallel Artificial Membrane Permeation Assay (Skin-PAMPA): A Pilot Study

Abstract: Introduction Retinol is known to have positive benefits on the skin including enhancements in barrier function, increased epidermal thickness, reductions in fine lines and wrinkles and reductions in hyperpigmentation. Improved methods to enhance the penetration of retinol are desirable. Methods A study was conducted to examine if addition of natural jojoba ( Simmondsia chinensis ) oil might help passively enhance the penetration of retinol thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Here, we utilized such a coculture system to which we added a hydrophobic PVDF membrane coated with a phospholipid. Such membranes have been extensively used to investigate the passive diffusion of skin actives, including the cosmetic ones, in PAMPAs [ 7 , 17 , 18 ]. However, to the best of our knowledge, this is the first time that the PAMPA was combined with life cell culture and used as an artificial stratum corneum –like barrier for bioactivity/cytotoxicity cell-based assays.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we utilized such a coculture system to which we added a hydrophobic PVDF membrane coated with a phospholipid. Such membranes have been extensively used to investigate the passive diffusion of skin actives, including the cosmetic ones, in PAMPAs [ 7 , 17 , 18 ]. However, to the best of our knowledge, this is the first time that the PAMPA was combined with life cell culture and used as an artificial stratum corneum –like barrier for bioactivity/cytotoxicity cell-based assays.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, natural antioxidant molecules have been shown to exhibit low dermal absorption properties and strategies to improve their cutaneous permeation, such as nano-encapsulation have been discussed [96,97]. In addition, the use of excipients such as jojoba oil was demonstrated in an in vitro study to potentiate the dermal absorption of retinol [98].…”
Section: Dermal Absorptionmentioning
confidence: 99%
“…For example, this model has been exploited by Rahma and colleagues [16] for the assessment of the permeation of phenoxyethanol, a common preservative ingredient in baby wipe formulations; notably, the authors observed a positive correlation for the total amount of permeated phenoxyethanol between this artificial membrane and porcine or human skin placed in a Franz diffusion cell, a widely used system to test drug permeation in vitro [16][17][18]. A skin PAMPA was also used to assess the penetration of retinol with the addition of natural jojoba oil as a penetration enhancer: interesting data were obtained on the transdermal delivery capability of jojoba oil since the retinol permeation registered was nearly 40-fold greater when associated with the oil, probably due to its ability to increase the fluidity of the lipid barrier [19]. However, skin PAMPAs have some drawbacks.…”
Section: Artificial Membranesmentioning
confidence: 99%